Enhancing the performance of NaNbO3 triboelectric nanogenerators by dielectric modulation and electronegative modification. (8th December 2017) - Lai, Meihui; Cheng, Lu; Xi, Yi; Wu, Yinghui; Hu, Chengguo; Guo, Hengyu; Du, Bolun; Liu, Guanlin; Liu, Qipeng; Liu, Ruchuan
Abstract: Increasing the triboelectric charge density on the friction layer of polydimethylsiloxane (PDMS) is a basic approach towards improving the output performance of a triboelectric nanogenerator (TENG). Most previous work focuses on the surface structure or dielectric properties, nonetheless, a few studies have focused on electronegative modification. NaNbO3 -PDMS TENG (N-TENG) devices are fabricated by dispersing cubic NaNbO3, which is a lead-free piezoelectric material with molecular oxygen dangling bonds on the surface of the crystal, into the PDMS at different mass ratios. When the mass ratio is 7 wt%, the maximum output performance of the N-TENG is obtained. The open-circuit voltage is 550 V, the short-circuit current is 16 µ A, and the effective power densities reach up to 5.5 W m −2 at a load resistance of 100 MΩ. The N-TENG has been used to assemble self-powered electronic watches and illuminate commercial light-emitting diodes, respectively. Its fundamental mechanism has also been discussed in detail from the perspective of dielectric modulation and electronegative modification. This N-TENG technology is revealed to be a splendid candidate for application in large-scale device fabrication, flexible sensors and biological devices thanks to its easy fabrication process, low consumption, high output power density and biocompatibility.